Adjuvant treatment with shenfu injection improve quality of life in chronic heart failure patients: A meta-analysis of randomized controlled trials - Junya Zhou; Songge Chen; Minghui Xu; Yali Guo; Xue Xia; Qingzhu Qin; Hongmei Zhang (Heliyon, 2023)
Objective: Shenfu Injection (SFI) derived from Shenfu decoction, has been widely used for treating heart failure in China. This meta-analysis aimed to assess the effect of SFI as an adjuvant therapy on quality of life in patients with chronic heart failure (CHF). Methods: A systematic literature search was conducted in CKNI, VIP, Wanfang, Sinomed, Cochrane Library, PubMed, and Embase database until March 16, 2023. Randomized controlled trials (RCTs) evaluating the effect of SFI plus conventional therapy versus conventional therapy alone for treating CHF were included. Outcome measures were quality of life defineded by the Minnesota Living with Heart Failure questionnaire (MLHFQ), left ventricular ejection fraction (LVEF), 6-min walking distance, and blood brain natriuretic peptide (BNP)/N-terminal pro-brain natriuretic peptide (NT-proBNP) level. Results: Thirteen RCTs enrolling 1042 CHF patients were included. SFI plus conventional therapy significantly reduced the total MLHFQ score (mean difference [MD] −8.69 points; 95% confidence intervals [CI] −13.46 to −3.91) compared with the conventional therapy alone. Moreover, adjuvant treatment with SFI significantly improved the 6-min walking distance (MD 65.42 m; 95% CI 44.23 to 86.62), LVEF (MD 3.89; 95% CI 1.03 to 6.75), and blood level of BNP/NT-proBNP (SMD -1.73; 95% CI -2.43 to −1.03). Conclusions: Adjuvant treatment with SFI can achieve additional benefits in improving quality of life and exercise tolerance in patients with CHF. These beneficial effects of SFI may correlate with its improving cardiac function. However, our findings should be interpreted with presence of significant heterogeneity and suboptimal quality of the analyzed trials.